Meta-analysis of Percutaneous vs. Surgical Approaches Radiofrequency Ablation in Hepatocellular Carcinoma - Huang, Xiaozhun; Liu, Yibin; Xu, Lin; Ma, Teng; Yin, Xin; Huang, Zhangkan; Wang, Caibin; Huang, Zhen; Bi, Xinyu; Che, Xu (Frontiers in Surgery, 2022)
Background: Radiofrequency ablation (RFA) is a curative modality for hepatocellular carcinoma (HCC) patients who are not suitable for resection. It remains controversial whether a surgical or percutaneous approach is more appropriate for HCC. Method: A search was performed on the PubMed, Web of Science, Embase, and Cochrane Library databases from the date of database inception until April 17, 2021. Studies reporting outcomes of comparisons between surgical RFA (SRFA) and percutaneous RFA (PRFA) were included in this study. The meta-analysis was performed using the Review Manager 5.3 and Stata 12.0 software. Result: A total of 10 retrospective studies containing 12 cohorts, involving 740 patients in the PRFA group and 512 patients in the SRFA group, were selected. Although the tumor size in PRFA group was smaller than the SRFA group (p = 0.007), there was no significant difference in complete ablation rate between the SRFA and PRFA groups (95.63% and 97.33%, respectively; Odds ratio [OR], 0.56; 95% confidence intervals [CI], 0.26–1.24; p = 0.15). However, the SRFA group showed a significantly lower local tumor recurrence than the PRFA group in the sensitivity analysis (28.7% in the PRFA group and 21.79% in the SRFA group, respectively; OR, 1.84; 95% CI, 1.14–2.95; p = 0.01). Pooled analysis data showed that the rate of severe perioperative complications did not differ significantly between the PRFA and SRFA groups (14.28% and 12.11%, respectively; OR, 1.30; 95% CI, 0.67-2.53; p = 0.44). There was no significant difference in the 1-, 3-, and 5-year overall survival rates, as well as the 1- and 3-year disease-free survival (DFS) between the PRFA and SRFA groups. The 5-year DFS of the PRFA group was significantly lower than the SRFA group (hazard ratio 0.73; 95% CI 0.54–0.99). Conclusion: Based on our meta-analysis, the surgical route was superior to PRFA in terms of local control rate. Furthermore, the surgical approach did not increase the risk of major complications.